Effect of Verbal Instruction on Motor Learning Ability of Anaerobic and Explosive Exercises in Physical Education University Students - Hermassi, Souhail; Sellami, Maha; Bouhafs, El Ghali; Schwesig, René; De Giorgio, Andrea (Frontiers in Psychology, 2019)
This study investigated the effect of motor learning with informational feedback into response to anaerobic exercises with and without motor learning tasks in handball physical education university students. Participants were randomly divided into two groups: experimental group (EG, n = 10) and control group (CG, n = 10). Measurements of T-half test, 15-m and 30-m sprints, and ZIG-ZAG test were assessed in both groups before (T1), between (T2) a 4-week intervention program, and after (T3) an 8-week intervention program, which included agility and speed teaching with (EG) or without (CG) informational feedback (i.e., verbal instruction). The test-retest reliability for all tests was excellent, and the ICC ranged from 0.76 (ZIG-ZAG test) to 0.99 (Agility T test). The interday measurement error was clearly below 1% in all tests (CV range: 0.2–0.8). Time effects for the Agility T test (p = 0.012, ηp2 = 0.245) and the 15-m sprint (p = 0.035, ηp2 = 0.190) were found. For the Agility T test, a total interaction effect (p = 0.001, ηp2 = 0.380) and a partial interaction effect were calculated between T2 and T3 (p < 0.001, ηp2 = 0.603). A large effect size (d = 0.87) was observed in the EG from T2 to T3. The second relevant (d ≥ 0.5) effect size was calculated for the parameter sprint 30 m. The CG showed a significant sprint performance reduction from T2 to T3 (d = −0.60; parameter: sprint 30 m). All other effect sizes were less than 0.44. The ZIG-ZAG test revealed the largest main and partial effect sizes for all parameters. The EG showed the largest improvement (d = 2.00) between T2 and T3. The results demonstrate that motor learning with informational feedback improves performances of Agility T test, sprint, and ZIG-ZAG performance. It appears that a well-formulated verbal instruction may induce performance enhancement in young trainees in educational environment.